Komunitas serangga hama padi rawa lebak yang ditanam dengan berbagai jarak tanam - Herlinda, Siti; Apryanti, Hesti; Susilawati, Susilawati; Anggraini, Erise (Jurnal Entomologi Indonesia, 2018)
Rice spacing can affect the species and populations of  insect pests. The closer spacing of rice are suitable for the habitats and niches of insect pests. This research was aimed to observe the community of insect pest on rice planted with various spacing regime. Field experiment was carried out on a-15 hectare rice field grown using various rice spacing: "˜tegel' (25 cm x 25 cm) and  legowo cropping of  4:1, 5:1, 6:1, and 7:1. Insect pests were collected using insect nets. All the insects found at a rice season were 27 species. The dominant species at vegetative stage of rice were Oxya chinensis (Thunberg), Acrida turrita (Linnaeus), Nilaparvata lugens (Stí¥l), Nephotettix virescens (Distant), and Cofana spectra (Distant), whereas at generative stage the dominated ones were Leptocorisa acuta (Fabricius) and Riptortus sp. The populations of N. lugens and N. virescens were not proven to be affected by rice spacing. The population of the both planthoppers were low and they did not become a key pest at fresh swamp ecosystems. The key insect pests was L. acuta and its population were  affected by the rice spacing.  The population of L. acuta was higher at rice with a more dense spacing, those were legowo cropping of  6:1, 7:1, and "˜tegel' compared to legowo cropping of 4:1 and 5:1. Therefore, legowo cropping of 4:1 or 5:1 should be applied  at the fresh swamp ecosystems to decrease the insect pests population.